Depois dos jesuítas: a economia colonial do Espírito Santo (1750-1800) - Conde, Bruno Santos (2011)
This work develops an effort in a way to characterize the economical reality of Espírito Santo during the second half of the eighteenth century, especially after the Jesuits expulsion, in 1759. This event was the main consequence of a whole process of changing within the administration of the Portuguese Empire, which also resulted in a renewal of the Portuguese interest on the colonial regions, as they were relegated to a second plan. In this context, the Portuguese crown implemented a series of actions to enhance the power on their vast possessions and, at the sime time, to enlarge their profits. Thus, this work attempts to elucidate the way that Espírito Santo dealt with two interconnected dynamics: the return of the Jesuits, whose work were so important if taken by their educational, economical and territorial occupation role, as well as the renewal of the Portuguese interest on the capitania, something that changed the character of its inception on the economical colony structure. Their arrival engendered a lot of elements of the process in course since 1750, but also started a new local era, which marks have shaped a different context from the one related to the second half of the Eighteenth Century. The historical sources of the Arquivo Histórico Ultramarino, as well as the post-mortem inventories, letters and extended bibliography served as bases to develop the ideas that are defended in this work.